1994
DOI: 10.1111/j.1432-1033.1994.tb18780.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterisation of a brain‐derived neurotrophic factor/ neurotrophin‐3 (BDNF/NT‐3) heterodimer

Abstract: The neurotrophins nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and neurotrophin-3 (NT-3) are known to exist in solution as non-covalently linked homodimeric proteins. The recent elucidation of the crystal structure of the NGF homodimer, as well as the conservation of structural motifs in the neurotrophins, raised the possibility that neurotrophin heterodimers might also occur. The formation of BDNFNT-3 heterodimers was explored using a vaccinia virus expression system. Upon co-infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…NT-4/BDNF Heterodimers Are Formed within Co-transfected Cells-Neurotrophins are normally released as homodimers, but co-expression of different members of the neurotrophin family can result in the formation of bioactive heterodimers (7,32). Previously, we reported that co-expression of NT-3 with BDNF results in secretion of BDNF/NT-3 heterodimers and that heterodimerizing NT-3 with BDNF redirects NT-3 from the constitutive to the regulated secretory pathway (2).…”
Section: Synthesis Processing and Glycosylation Of Pro-nt-4 In Vi-mentioning
confidence: 99%
“…NT-4/BDNF Heterodimers Are Formed within Co-transfected Cells-Neurotrophins are normally released as homodimers, but co-expression of different members of the neurotrophin family can result in the formation of bioactive heterodimers (7,32). Previously, we reported that co-expression of NT-3 with BDNF results in secretion of BDNF/NT-3 heterodimers and that heterodimerizing NT-3 with BDNF redirects NT-3 from the constitutive to the regulated secretory pathway (2).…”
Section: Synthesis Processing and Glycosylation Of Pro-nt-4 In Vi-mentioning
confidence: 99%
“…The retinal concentration of BDNF after injection was ϳ100 -500 times higher (total BDNF ϭ 5-10 ng) than the concentration of endogenous BDNF at this age (total BDNF/retina Ϸ 50 pg) ; J. E. Johnson, Wake Forest University, personal communication). Alternative explanations of BDNF immunoprecipitation with trkC antibodies include the possibilities that heterodimers of exogenous BDNF and endogenous NT-3 form that bind to trkC (Jungbluth et al, 1994;Philo et al, 1994), that trk and p75 may coprecipitate (Huber and Chao, 1995), or that the trkC antibody may recognize certain isoforms of trkB (Garner et al, 1996) although it does not recognize the predominant form of trkB (Lefcort et al, 1996).…”
Section: Cross-linking and Immunoprecipitation Of Bdnf To P75 And Trkmentioning
confidence: 99%
“…To determine the localization of BDNF at the protein level, we used a previously characterized affinitypurified serum raised against a peptide (B6) of the N-terminal portion of BDN F. This antibody recognizes BDN F in Western blots (Jungbluth et al, 1994) and does not cross-react with NT-3. When this antibody was applied to the retinae of 8.5-d-old chick embryos, the GCL, but no other layer in the retina, was heavily labeled (Fig.…”
Section: Bdnf Immunocytochemistry In the Retinamentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotrophins naturally form homo-dimers and have been shown to form hetero-dimers experimentally, though the functionality of hetero-dimers is somewhat in question [48,49].…”
Section: B Cell Malignanciesmentioning
confidence: 99%